Odiai-vos uns aos outros : cenas do discurso de ódio religioso no Instagram - Gregory Pablo Rial Araújo (2024)
Hate speech against LGBTQIA+ individuals in Brazil has been increasing over time, often motivated by religious reasons. The convergence of various social and cultural factors, such as the intense process of mediatization and the platformization of human relations, the neoconservative wave in politics, the capitulation of increasingly violent and morally rigid Christian religious discourse by far-right political currents, and the increasingly intensive and qualified presence of these religious and political currents on the internet lead us to believe that the proliferation of religiously motivated anti-LGBTQIA+ hate speech is a significant phenomenon in the Brazilian social dynamics, with digital social networks playing a non-marginal role in this process. Therefore, this study aims to investigate how anti-LGBTQIA+ hate speech rooted in Christian religious beliefs is textually manifested on Instagram, considering visibility regimes and platform-specific features. The goal is to understand how the frameworks of hate speech are semiotically materialized in Instagram textuality, evoking signs and meanings that communicate hate and repulsion towards LGBTQIA+ lives, thus producing and reproducing violence from a Christian religious base. To this end, the first chapter aims to understand the legal, communicative, and textual aspects of hate speech, also addressing issues related to the processes of mediatization, technologization, and platformization of everyday life. The second chapter identifies the frameworks of hate speech through a theoretical and hermeneutic exercise of authors from various fields such as Carlin Emcke, Kolnai, Levinas, Adorno, Foucault, Butler, Freud, among others. Thus, three frameworks of hate speech are developed: affective-emotional; epistemological-metaphysical; and sociopolitical. The third chapter outlines the methodology of the empirical research, which consists of a three-pronged methodological approach: the theory of affects in research, guided by Moriceau, Marques, Martino, and Mendonça for navigating the platform and monitoring profiles; the method of the scene proposed by Rancière, as a way of organizing textuality qualitatively; and the analysis of visual textuality by Gonzalo Abril, based on the categories of visuality—gaze—imaginary. In the fourth, fifth, and sixth chapters, three textual scenes of hate speech are developed with an analysis of the textual corpus gathered for the thesis, consisting of 50 posts. These scenes address issues such as the selective use of signs that associate LGBTQIA+ individuals with evil and the devil, the use of language that fuels moral panic, the theoretical construction of gender ideology, techniques of exclusion and symbolic violence against LGBTQIA+ individuals in churches, and the steering of politics and the acquisition of civil rights towards a conservative religious bias. Finally, we conclude that on Instagram, hate speech conforms to a visibility regime that values the subtlety of signs, which does not make it less violent, and demonstrate that Christian-based homophobia operates in various forms in the hostility and violence against those who do not fit into its worldview.